Psychological Impact of Primary Screening (PIPS) for HPV: a protocol for a cross-sectional evaluation within the NHS cervical screening programme. Issue 12 (23rd December 2016) - McBride, Emily; Marlow, Laura; Forster, Alice S; Moss, Sue; Myles, Jonathan; Kitchener, Henry; Patnick, Julietta; Waller, Jo
Abstract : Introduction: The NHS Cervical Screening Programme is now using human papillomavirus (HPV) testing as the primary test in six sentinel sites in England, with the intention of rolling this out across the whole of England. Previous research evaluating HPV testing in the cervical screening context suggests that an HPV-positive result may increase anxiety beyond that associated with abnormal cytology, but this has not been explored in the context of primary HPV testing. The main aim of this study is to explore the impact of the HPV primary screening programme on anxiety and distress. Methods and analysis: A cross-sectional between-groups design (total N ∼ 673) will be employed to assess the psychological impact of different HPV and cytology results at three time points: shortly after receiving the results, and 6 and 12 months later. Women will fall into one of six groups based on their screening results. The primary outcomes will be anxiety and general distress. Secondary outcomes will include understanding of screening results, perceived risk of cervical cancer, psychosexual functioning, intention to attend future screening and knowledge of HPV. General linear modelling will be used to test for differences between groups and changes over the three time points. Ethics and dissemination: Health Research Authority approval was received on 26 September 2016. Ethical approval was received from London- Surrey Borders NHS Research Ethics Committee on 30 August 2016. Section 251 approval was received from the Confidentiality Advisory Group on 24 August 2016. Results will be disseminated via peer-reviewed publication and presentation at national and international conferences.